Analysis of Factors Affecting The Effectiveness of Land And Building Tax Revenue in Rural-Urban Areas in South Buru District - Afifudin Latuconsina; Djufri Rays Pattilouw; Izaac Tonny Matitaputty (LP2M IAIN Palopo, 2026)
The realization of Rural-Urban Land and Building Tax (PBB-P2) revenue in South Buru Regency is often not commensurate with the existing potential. This condition indicates obstacles in optimizing regional revenue sourced from the tax sector. This study aims to analyze the factors that influence the effectiveness of PBB-P2 revenue in South Buru Regency. The factors studied include taxpayer compliance, the tax collection system, and the quality of tax apparatus services. The study used a quantitative approach with a regression analysis method to examine the influence of these variables on the effectiveness of PBB-P2 revenue. The results show that the level of tax revenue effectiveness from 2020 to 2024 is classified as ineffective only in 2022, because in that year the effectiveness value is in the less effective category. The results of the partial multiple linear regression test indicate that the variables of taxpayer compliance, the tax collection system, and service quality have no significant effect on the effectiveness of tax revenue in South Buru Regency. However, all three variables simultaneously have a significant effect on the effectiveness of tax revenue in the region. Thus, the South Buru Regency Government needs to improve taxpayer compliance, the collection system, and the quality of services so that the effectiveness of tax revenue is more optimal.